The framework and syllabus of the optional course in physical education, «Phygital-sport» - Sidorov S.S.; Sushchenko V.P.; Usovich A.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to support the educational framework of the optional physical education course «Phygital Sport». Methods and structure of the study. The framework is built upon a thorough examination of educational and instructional materials on the arrangement of educational and training processes and comprehensive pedagogical assessment in the following sports: computer gaming, basketball (3x3), mini-football, and track and field. In the creation of the pedagogical model, we adhered to the following principles: incrementalism, coherence, engagement, balanced development, and gamification. Results and conclusions. The fundamental aspects of the curriculum, the allocation of time by subject and semester, the typical format of the lessons, the logistical support for the course, and the criteria for evaluating the quality of the course are outlined. The outcomes of this research can be applied in the implementation of physical education programs that incorporate phygital sports in educational settings.